The purloining of Prince Oleomargarine - Twain, Mark, 1835-1910; Stead, Philip Christian (Doubleday Books for Young Readers, 2017)
"Based on a set of unfinished Mark Twain notes for a children's story, this is the tale of Johnny, a young boy with a magical ability to speak to animals who sets off to rescue a stolen prince"--